Evaluation of correlation between cephalometric variables and internal derangement of temporomandibular joint in asymptomatic class II division I high angle patients using Helical computed tomography - Diravidamani Kamatchi; Vasanthan Palanivel; Sathesh Kumar Sivalingam (SRM Journal of Research in Dental Sciences, 2013)
Introduction: The aim of this study was to identify the presence of articular disk displacement using helical computed tomography (CT) in asymptomatic Class II Division I patients and to find a correlation between internal derangement of temporomandibular joint (TMJ) and certain lateral cephalometric variables. Materials and Methods: After screening 578 patients in the age group 18-25 years, 30 patients who met the case selection criteria and willing to cooperate were included in the study. Frontal and profile photographs and lateral cephalograms were taken. Helical CT of TMJ were taken and the disk tissue of the joint was analyzed. Composite cephalometric analysis was performed to evaluate cranial base, vertical skeletal relationships, maxillary and mandibular skeletal relationships, and dental relationships. Results: Mean and standard deviation were estimated from the sample in each group. Mean values were compared using Student′s independent t-test. Patients with disk displacement have shorter anterior and posterior cranial base, small posterior facial height (PFH), backward rotation of mandible, decreased mandibular body length, and an increase in proclination of lower incisors. Conclusion: Certain cephalometric variables correlate well with helical CT findings of patients with internal dernagement of TMJ (TMJ ID), and thus could assist in identifying patients with potential TMJ disorders.